Temperature Dependence of Thermophysical Properties of Full-Scale Corium of Fast Energy Reactor - Mazhyn K. Skakov; Nurzhan Ye. Mukhamedov; Alexander D. Vurim; Ilya I. Deryavko (Science and Technology of Nuclear Installations)
For the first time the paper determines thermophysical properties (specific heat capacity, thermal diffusivity, and heat conductivity) of the full-scale corium of the fast energy nuclear reactor within the temperature range from ~30°С to ~400°С. Obtained data are to be used in temperature fields calculations during modeling the processes of corium melt retention inside of the fast reactor vessel.